2020
DOI: 10.3390/ani10122441
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Thermotolerance in Dorper and Second-Cross (Poll Dorset/Merino × Border Leicester) Lambs

Abstract: The objective of this study was to compare the thermotolerance of second-cross (SC; Poll Dorset × Merino × Border Leicester) and Dorper lambs. Dorper and SC lambs (4–5 months of age) were subjected to cyclic heat stress (HS) (28–40 °C). The temperature was increased to 38–40 °C between 800 and 1700 h daily and maintained at 28 °C for the remainder of the day (30–60% relative humidity (RH)) in climatic chambers for 2 weeks (n = 12/group), with controls maintained in a thermoneutral (TN) (18–21 °C, 40–50% RH) en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 67 publications
2
11
1
1
Order By: Relevance
“…The increase in RR, RT and ST with exposure to a HW observed in this experiment agrees with previous research on HS in sheep [9,[24][25][26]. The increase in RT is a commonly used indicator of HS observed when ambient temperature exceeds the species temperature threshold, and the animal can no longer maintain its core body temperature.…”
Section: Temperature-humidity Index and Physiological Parameterssupporting
confidence: 88%
See 2 more Smart Citations
“…The increase in RR, RT and ST with exposure to a HW observed in this experiment agrees with previous research on HS in sheep [9,[24][25][26]. The increase in RT is a commonly used indicator of HS observed when ambient temperature exceeds the species temperature threshold, and the animal can no longer maintain its core body temperature.…”
Section: Temperature-humidity Index and Physiological Parameterssupporting
confidence: 88%
“…We have previously shown that the muscle pH and meat quality in lamb was not affected after 2 weeks or 1 week controlled HS exposure (28-40 • C, 30-40% RH) [9,38]. Similar to the current study, we had observed that the lambs' physiological and blood gas parameters were significantly affected by HS but not the meat quality and muscle pH [26]. These results also agree with previous work of Lowe, et al [7], who reported that 12 h of HS did not change sheep meat quality.…”
Section: Postmortem Muscle Glycolysis and Meat Qualitysupporting
confidence: 88%
See 1 more Smart Citation
“…Continuous selection for high-yielding wool and meat traits has made the sheep population more susceptible to summer heat stress (HS) due to associated feed and metabolic energy requirements [ 1 , 2 ]. Many studies have reported a HS-associated elevation in the thermoregulatory responses [ 3 , 4 , 5 ] and a decline in the production parameters of sheep [ 6 ]. Often, there are reports of impaired reproduction variables such as pregnancy rate, embryo survival, and lambing rates [ 7 , 8 ]; therefore, researchers and farmers have increased attention into the use of feed or feed additives that can mitigate the seasonal effects of heat while using livestock with a high genetic gain [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dorper is the result of the cross between Dorset Horn and Blackhead Persian, original transboundary breeds from South Africa. It presents high productivity with excellent performance, conformation, and uniform carcasses associated with meat quality (Ocak et al 2016;Issakowicz et al 2018;Joy et al 2020). Locally adapted breeds, such as Santa Inês, showed small bodyweight sizes compared to exotic specialized breeds (Malhado et al 2009).…”
Section: Introductionmentioning
confidence: 99%